Körperbild und psychische Komorbidität bei Patienten mit somatoformen autonomen Funktionsstörungen des oberen und unteren Gastrointestinaltrakts - Martens, Ute; Czerwenka, Susanne; Schrauth, Markus; Kowalski, Axel; Enck, Paul; Hartmann, Mechthild; Zipfel, Stephan; Sammet, Isa (Zeitschrift für psychosomatische Medizin und Psychotherapie, 2010)
The significance of body perception and satisfaction with one's own body in patients with somatoform disorders of the upper and lower gastrointestinal tract is presently unknown, as is the relationship thereof to depression and other psychiatric comorbidities.
Online veröffentlicht im April 2014
Gesehen am 23.05.2023